Möbius bridges. Issue 2 (3rd July 2018) - Séquin, Carlo H.
ABSTRACT: Key concepts and geometrical constraints are discussed, which allow the construction of a usable bridge that is topological equivalent to a Möbius band. A multi-year search in publications and on the Internet for real-world bridges that meet these requirements has not identified a single clean construction that warrants the designation 'Möbius bridge, ' but a few promising designs can be found. Several simple but practical designs are presented here. GRAPHICAL ABSTRACT: